Modulating the Electronic Structures of Dual‐Atom Catalysts via Coordination Environment Engineering for Boosting CO2 Electroreduction - Gong, Yun‐Nan; Cao, Chang‐Yu; Shi, Wen‐Jie; Zhang, Ji‐Hong; Deng, Ji‐Hua; Lu, Tong‐Bu; Zhong, Di‐Chang (Angewandte Chemie International Edition, 2022)
Dual‐atom catalysts (DACs) have emerged as efficient electrocatalysts for CO2 reduction owing to the synergistic effect between the binary metal sites. However, rationally modulating the electronic structure of DACs to optimize the catalytic performance remains a great challenge. Herein, we report the electronic structure modulation of three Ni2 DACs (namely, Ni2−N7, Ni2−N5C2 and Ni2−N3C4) by the regulation of the coordination environments around the dual‐atom Ni2 centres. As a result, Ni2−N3C4 exhibits significantly improved electrocatalytic activity for CO2 reduction, not only better than the corresponding single‐atom Ni catalyst (Ni−N2C2), but also higher than Ni2−N7 and Ni2−N5C2 DACs. Density functional theory (DFT) calculations revealed that the high electrocatalytic activity of Ni2−N3C4 for CO2 reduction could be attributed to the electronic structure modulation to the Ni centre and the resulted proper binding energies to COOH* and CO* intermediates. Three Ni2 dual‐atom catalysts (DACs) with electronic structures tailored by the regulation of the coordination environment of Ni atoms, have been prepared for electrocatalytic CO2 reduction. The optimal Ni2−N3C4 exhibits the highest performance for the reduction of CO2 to CO, highlighting the significance of the electronic structure for electrocatalytic CO2 reduction in DACs.